Determinant Factors for Apartment Location-Decisions in Surabaya - Nilam Atsirina Krisnaputri; Kovic Salim (International Journal of Built Environment and Scientific Research, 2021)
Surabaya which has been growing by trading, office and industry activities, requires a representative residential. In addition, the increase of population growth requires it as well. However, due to limited amount of land in Surabaya, government opens wide opportunities in developing apartments. Ease of permitting in apartments development and coupled with increasing of apartments demand manifold both in terms of developers (investor) nor the buyer has encouraged the location of apartments grow at random. The spread of the location is important in order to avoid build up that can give the layer of building and environmental dimensions. This study is conducted to explore issues and approaches of factors which giving effect on apartment location decisions by using literature review method. As a result, factors for apartment location-decisions are consist of (1) physical factors, (2) accessibility factor, and (3) land and legal factor.